Região de Araraquara: elementos para pensar um indicador sobre vocação produtiva grícola - Campos, Ricardo Luiz Sapia de [UNESP] (My University, 2012)
This paper seeks to explore some key elements that are relevant to improve overall productivity including, particularly, the small agricultural enterprises in the so-called "region of Araraquara". Location and infrastructure, among other factors, are of paramount importance; however I endeavor to highlight those, which I consider are the most significant and refer to aspects of cognitive and immaterial labor in the sense that its products are intangible, such as knowledge, communication, interaction, focusing on institutional collaborative activities and productive resistance.

Busco apontar e discutir alguns elementos que considero centrais para pensar o desenvolvimento produtivo em geral, e o desenvolvimento de pequenos empreendimentos agrícolas da chamada "região de Araraquara" em particular. Considero e relevo fatores como localização, infra-estrutura, dentre outros mais objetivos, todavia me atenho mais pontualmente aqueles de cunho imaterial e cognitivo, com destaque para o saber, conhecimento, interação, comunicação, e particularmente a institucionalidade histórica de práticas cooperadas e de resistência produtiva.
Keywords: Local Development; Knowledge and Understanding; Reciprocity; Agricultural Entrepreneurship; Agricultura alternativa; Desenvolvimento local; Resistencia produtiva; Ruralidade; Trabalho